Proton-Sensing G Protein-Coupled Receptors and Their Potential Role in Exercise Regulation of Arterial Function - Fengzhi Yu; Dandan Jia; Ru Wang (Biomolecules)
During periods of exercise, the primary cause of metabolic acidosis is the accumulation of lactate from anaerobic metabolism, whereas a transient increase in CO2 triggers a mild respiratory acidosis through the production of carbonic acid (H2CO3). The combined effects of these reactions result in a slight acidifying shift in arterial blood pH. Proton-sensing G protein-coupled receptors (including GPR68, GPR4, GPR132, and GPR65) represent the primary receptors within the body for detecting alterations in extracellular proton concentrations. These receptors have been demonstrated to possess potential roles in mechanosensation, intestinal inflammation, oncoimmunological interactions, hematopoiesis, as well as inflammatory and neuropathic pain. Recent studies have shown that the activation or inhibition of these receptors modulates a number of arterial functions, including angiogenesis, arterial relaxation, and arterial inflammation. It is well established that moderate exercise has a beneficial effect on the regulation of arterial function. This study examines the effect of exercise on proton concentrations in the microenvironment of the organism and its influence on proton-sensing G protein-coupled receptors located on cell membranes, as well as possible mechanisms involved in the regulation of arterial function. The objective is to present novel perspectives for the exploration of potential drug targets for the prevention and treatment of arterial dysfunction and the development of exercise regimens.